Meningkatkan financial dan management capability lembaga grantee menggunakan pendekatan model nupas: Non-us organization pre-award survey - Rini Oktavia; Unggul Purwohedi; I Gusti Ketut Agung Ulupui (AKURASI: Jurnal Riset Akuntansi dan Keuangan, 2023)
This study aims to know more readiness of a USAID grant recipient institution, or we can call as a grantee. To attest that NUPAS (Non-US organization pre-award survey) model approach can improve the financial and management capability of the grantee. Furthermore, to provide input to the grantee in improving its financial and management capability. In a case study at a USAID grant recipient institution, that is ‘Alpha’ study center in Salatiga, the researcher found it experiences difficulty in identifying financial and management capability, which impacts the un-complied financial report with the grantor requirement that effecting the grant disbursement which automatically will be impacting the outcome of the project. This research is generally expected as the reference for all grantees in Indonesia who want to apply to the grantor to know their readiness to be a grant recipient and for X study center in particular. Public interest statement Grants are the largest source of income for non-profit organizations. It must be in the public interest but inreality there is frequently misuse of grant funds. The researchers try to investigate how grantee can impove its Financial and Management Capability. By using the NUPAS model, a guideline from donor agency to measure it, the findings shows the institutions where doing the case study can identify deficiencies to improve Financial and Management Capabilities. In the end, appropriate recommendations have been forwarded in this paper. Article History Received 08 Jan 2023 | Revised 18 Jan 2023 | Accepted 23 Jan 2023 | Online First 03 Feb 2023